2012
DOI: 10.1007/s10535-012-0034-1
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrin and proline content in Brassica napus and B. carinata under cold stress at two irradiances

Abstract: The accumulation of cold-induced dehydrin and proline was related to the frost tolerance (FT) in several Brassica species or cultivars. A dehydrin of molecular mass 47 kDa was detected in the leaves of an Ethiopian mustard (B. carinata) and a pair of dehydrins of similar molecular mass in the three (two winter, one spring) oilseed rape (B. napus) cultivars, when plants were maintained at 4 °C for one-month under two different irradiances. More dehydrin was accumulated in oilseed rape than in Ethiopian mustard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 40 publications
(33 reference statements)
2
6
0
Order By: Relevance
“…Previous reports showed that various stress-responsive metabolites of plants were synthesized from amino acid metabolic pathways, suggesting that amino acid metabolism plays an important role in response to stress in plants [ 69 ]. For instance, proline accumulation in many plants is a common physiological response to abiotic stresses, such as LT, drought, and high salinity [ 70 72 ]. Proline is known to stabilize proteins, membranes, and subcellular structures, and protect cellular functions by scavenging ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that various stress-responsive metabolites of plants were synthesized from amino acid metabolic pathways, suggesting that amino acid metabolism plays an important role in response to stress in plants [ 69 ]. For instance, proline accumulation in many plants is a common physiological response to abiotic stresses, such as LT, drought, and high salinity [ 70 72 ]. Proline is known to stabilize proteins, membranes, and subcellular structures, and protect cellular functions by scavenging ROS.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of its accumulation during cold acclimation occurs, e.g. in Brassica napus [28], Chrysanthemum dichrum [11], and Poncirus trifoliate [42]. Also, transgenic tobacco ( Nicotiana tabacum ) over-expressing crucial genes for proline synthesis showed greater cold tolerance than the wild type [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, while it is recognized that proteins are key structural and functional elements within the cell, such as structural components of membranes, transporters, enzymes, and receptors, influencing and determining a variety of metabolic processes within the cell, including growth and development processes and cold resistance [ 57 , 58 , 59 , 60 ], till now, their metabolic processes, compositional changes, and relationships with plant resistance and preparation for wintering have not been fully investigated and disclosed. Experiments, especially on herbaceous plants, are usually carried out by simulating the process of cold acclimation, i.e., by changing the temperature and the duration of the photoperiod under control conditions [ 29 , 47 , 61 ]. Previous studies have been shown changes in herbaceous plant proteins under natural conditions, including common wheat [ 62 ] and alfalfa [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Native electrophoresis, denaturing SDS-PAGE, and immunoblotting methods were performed to confirm changes in the protein composition and their metabolic processes in the winter oilseed rape cultivars. In contrast to the work of other authors [ 47 , 61 ], in which only the soluble protein fractions were analyzed, in the current study we also analyzed changes in the proteins from the cell membrane component during the oilseed rape natural cold acclimation. It had been reported that changes in the protein composition from the cell membranes during the period of cold acclimation in the organs which are important for wintering in herbaceous plants (the terminal bud and root collar) need to be analyzed due to changes in the condition and functional properties of membranes [ 11 , 56 , 68 ].…”
Section: Discussionmentioning
confidence: 99%